OPTIMALISASI PELATIHAN DIGITAL DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM - Ahmad Khori; M Sukron; Cucu Hasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The swift progression of information and communication technology within the Society 5.0 era necessitates that Islamic Education (PAI) teachers evolve beyond traditional pedagogical frameworks and proactively cultivate digital literacy. This study examines the strategic optimization of digital training programs designed to enhance the pedagogical competence and professionalism of PAI teachers. Employing a descriptive qualitative approach with a case study design, data were gathered through in-depth interviews, participatory observations, and comprehensive documentation of digital training initiatives attended by PAI educators. The findings indicate that structured, practice-oriented, and continuous digital training significantly bolsters teachers' proficiency in developing interactive learning media (utilizing applications such as Canva, Quizizz, and AI-driven platforms) and managing virtual classrooms via Learning Management Systems (LMS). Pedagogical advancements are demonstrated by the teachers' capability to deliver contextualized, innovative content tailored to the characteristics of Generation Z and Alpha. Concurrently, professional growth is reflected in their autonomous capacity to curate valid, diverse digital learning repositories. The primary obstacles identified include inadequate supporting infrastructure and baseline disparities in initial digital literacy among participants. This study concludes that maximizing the impact of digital training requires a sustained, synergistic collaboration between the Ministry of Religious Affairs, regional education departments, school administrators, and the personal professional commitment of the teachers.